Multiple Virus Infections in Western Honeybee (Apis mellifera L.) Ejaculate Used for Instrumental Insemination - Jana Prodělalová; Romana Moutelíková; Dalibor Titěra (Viruses, 2019)
Instrumental insemination of Apis mellifera L. queens is a widely employed technique used in honeybee breeding that enables the effective control of mating. However, drone semen represents a potential source of honeybee viruses. In this study, 43 semen doses collected from apparently healthy drones, and consequently used in instrumental insemination, were analysed using PCR or RT-PCR to detect the presence of viral genome of 11 honeybee viruses. In 91% of samples, viral infection was detected. The survey revealed genomes of five viruses, namely Deformed wing virus (DWV), Acute bee paralysis virus (ABPV), Black queen cell virus (BQCV), Sacbrood virus (SBV), and A. mellifera filamentous virus (AmFV) in 84%, 19%, 14%, 2%, and 67% of samples, respectively. Single infection (30% of samples) as well as multiple infection (61% of samples) of two, three or four pathogens were also evaluated. To the best of our knowledge, this is the first study describing the presence of the BQCV and SBV genome sequence in drone ejaculate. Phylogenetic analysis of BQCV partial helicase gene sequence revealed the high similarity of nucleotide sequence of described Czech strains, which varied from 91.4% to 99.6%. The findings of our study indicate the possibility of venereal transmission of BQCV and SBV.